2014
DOI: 10.7717/peerj.439
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory generation of new parthenogenetic lineages supports contagious parthenogenesis inArtemia

Abstract: Contagious parthenogenesis—a process involving rare functional males produced by a parthenogenetic lineage which mate with coexisting sexual females resulting in fertile parthenogenetic offspring—is one of the most striking mechanisms responsible for the generation of new parthenogenetic lineages. Populations of the parthenogenetic diploid brine shrimp Artemia produce fully functional males in low proportions. The evolutionary role of these so-called Artemia rare males is, however, unknown. Here we investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…This phenomenon, known as contagious parthenogenesis (Simon et al 2003), has been analyzed in detail in diploid parthenogenetic Artemia (brine shrimp) lineages (Maccari et al 2013) and in Daphnia pulex (Paland et al 2005). The formation of parthenogenesis of this type has also been experimentally demonstrated in the laboratory in Daphnia (Innes and Herbert 1988), aphids (Blackman 1972) and Artemia (Maccari et al 2014).…”
Section: Evolutionary Significance Of Rare Males and Diploid Femalesmentioning
confidence: 96%
“…This phenomenon, known as contagious parthenogenesis (Simon et al 2003), has been analyzed in detail in diploid parthenogenetic Artemia (brine shrimp) lineages (Maccari et al 2013) and in Daphnia pulex (Paland et al 2005). The formation of parthenogenesis of this type has also been experimentally demonstrated in the laboratory in Daphnia (Innes and Herbert 1988), aphids (Blackman 1972) and Artemia (Maccari et al 2014).…”
Section: Evolutionary Significance Of Rare Males and Diploid Femalesmentioning
confidence: 96%
“…The molecular divergence analysis has indicated that a recent population expansion in A. urmiana and "Eurasian Haplotype Complex" occurred in the Pleistocene (1.72 Mya) and Holocene (0.84 Mya), respectively. Males of parthenogenetic Artemia (produced only by diploids; Saleem Chang et al 2017) are fertile when mating with bisexual A. sinica, A. tibetiana, A. urmiana and KAZ (Cai 1993;Liu et al 2007;Maccari et al 2014), but not fertile when mating with the female of the other bisexual species (Mac-Donald and Browne 1987). Parthenogenetic females mating with males produce only parthenogenetic offspring (Barigozzi 1974).…”
Section: A Salina Var N/a N/a N/amentioning
confidence: 99%
“…Alternatively, the generation of new asexual genotypes can still be ongoing, for instance via mutation [64], continuing hybridization of, or with, the sexual parents [65], contagious asexuality via endosymbiont transmission [66] or rare crossings with sexuals (e.g. [42] in hermaphrodite flatworms; [67] in Daphnia and [68] in Artemia owing to rare parthenogenetic sons), or forms of 'parasex' [69] such as horizontal gene transfer between individuals (bdelloid rotifers, see [70]) or introgression of environmental DNA (anhydrobiotic rotifers or tardigrades [71]). …”
Section: (A) a Marginal Habitat?mentioning
confidence: 99%